ISOLATION OF Aspergillus niger FROM Allium cepa BULB AND PRODUCTION OF CITRIC ACID FROM IT - DILENDRA CHANDRAKER; SHWETA SAO; YOGESH KUMAR DESHMUKH; LEENA VERMA; PANKAJ K. SAHU (International Journal of Pharma and Bio Sciences, 2014)
The fungal pathogen, Aspergillus niger is known to cause decaying in storage onion bulbs and causes black mold not only in Allium cepa but also fungal disease in Arachis and Vitis spp. Post harvest disease of onion causes by Aspergillus niger may be observed between bulb scales. Infection of onion seedlings by A. niger can become systemic, manifesting only when conditions are conducive. In present studies is focused on the citric acid producing organisms were isolated from Allium cepa bulb and identified morphological characteristics by the microscopic and identified by amylase production test. The isolated fungal species were screened on the acid production using Czapek - dox agar medium and citric acid produced by using Aspergillus niger.